ENGLISH TEXTBOOK ANALYSIS “SMART ENGLISH BOOK” GRADE XII SENIOR HIGH SCHOOL BASED ON THE 2013 CURRICULUM AT SMAN 1 MERTOYUDAN - Fauzi, Muhammad Fikar (Journal of Research on Applied Linguistics, Language, and Language Teaching, 2024)
AbstractTo facilitate their teaching and learning processes, every teacher and student requires textbooks. However, not all textbooks released are appropriate for students' needs and have good qualities. This research analyses an English textbook entitled "Smart English Book" for grade XII Senior High School based on the 2013 Curriculum at SMAN 1 Mertoyudan. The purpose of this research is to find topics and resources in an English textbook entitled “Smart English Book” that are aligned with the 2013 Curriculum's basic competencies. A descriptive qualitative research approach is used in this research. The English textbook "Smart English Book" was used as the data source for this study. The researchers approach of data collection is document analysis. Finally, the researchers reached the conclusion that not all themes and materials in every unit of that English textbook are suitable for the 2013 curriculum's basic competency. That English textbook is divided into four units, each with its own set of themes and materials. There are three units (7.5 percent) of each unit's four themes that are appropriate with the 2013 Curriculum's basic competences, and there are two units (50 percent) of each unit's materials that are appropriate with the 2013 Curriculum's basic competencies. Keywords : textbook in English, basic competency, 2013 curriculum, theme, and material